2012
DOI: 10.3109/15376516.2012.727198
|View full text |Cite
|
Sign up to set email alerts
|

Liver iron and serum ferritin levels are misleading for estimating cardiac, pancreatic, splenic and total body iron load in thalassemia patients: factors influencing the heterogenic distribution of excess storage iron in organs as identified by MRI T2*

Abstract: A comparative assessment of excess storage iron distribution in the liver, heart, spleen and pancreas of β-thalassemia major (β-ΤΜ) patients has been carried out using magnetic resonance imaging (MRI) relaxation times T2*. The β-ΤΜ patients (8-40 years, 11 males, 9 females) had variable serum ferritin levels (394-5603 μg/L) and were treated with deferoxamine (n = 10), deferiprone (n = 5) and deferoxamine/deferiprone combination (n = 5). MRI T2* assessment revealed that excess iron is not proportionally distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 42 publications
2
52
0
Order By: Relevance
“…Variations in compensatory mechanisms and alternative metabolic pathways which are in operation in affected cells and tissues may contribute to minimising the severity of FA [85] . Similar variations are observed in other inherited and metabolic diseases including TM and hereditary haemochromatosis [13,62,[85][86][87] . Deficit of frataxin is mostly related to many abnormalities associated with mitochondrial structure and function.…”
Section: Ataxiasupporting
confidence: 50%
See 1 more Smart Citation
“…Variations in compensatory mechanisms and alternative metabolic pathways which are in operation in affected cells and tissues may contribute to minimising the severity of FA [85] . Similar variations are observed in other inherited and metabolic diseases including TM and hereditary haemochromatosis [13,62,[85][86][87] . Deficit of frataxin is mostly related to many abnormalities associated with mitochondrial structure and function.…”
Section: Ataxiasupporting
confidence: 50%
“…The quality of life and survival of TM patients have increased substantially in the last 20 years as a consequence of the introduction of effective therapeutic postnatal measures and especially diagnostic advances in the estimation of iron overload using the MRI T2* and T2 techniques and especially the effective treatment of iron overload with L1 and its combinations [86,132] . These changes and related improvements are more obvious in Cyprus and other countries where government health authority intervention is significant and appropriate by-laws as well as appropriate procedures are implemented using effective organisational health structures.…”
Section: Future Prospects In the Treatment Of Thalassaemia And Friedrmentioning
confidence: 99%
“…Patients with mild, moderate and severe cardiac iron overload (T2* 12-20, 8-12 and less than 8 ms, respectively) had impaired LVEF in [56] (r 2 = 0.003, P = 0.04) TM/776 patients Retrospective Significant relationship between cardiac R2* and ferritin / Marsella et al [59] (r = -0.359, P < 0.0001) TM/167 patients Prospective Myocardial T2* was correlated with serum ferritin / Tanner et al [60] (r = -0.34, P < 0.001) TM/19 patients, SCD/17 patients Cross sectional Cardiac 1/T2* was correlated with ferritin level / Wood et al [61] (r 2 = 0.33, P = 0.01) TM/106 patients Prospective No significant correlation between heart T2* and serum ferritin × Anderson et al [16] TM/60 patients Prospective Serum ferritin did not correlate with cardiac iron values × Merchant et al [57] TM/20 patients Prospective No correlation between serum ferritin and cardiac T2* × Kolnagou et al [58] TM/47 patients Retrospective Cardiac T2* was not associated with the serum ferritin × Bayraktaroğlu et al [22] TM: Thalassemia major; SCD: Sickle cell disease. TM/776 patients Retrospective Significant correlation between LVEF and cardiac R2* (r = -0.327, P < 0.0001) / Marsella et al [59] TM/106 patients Prospective Significant correlation of myocardial T2* below 20 ms with LVEF (r = 0.61, P < 0.0001), LVESVi (r = 0.50, P < 0.0001), and LV mass index (r = 0.40, P < 0.001) / Anderson et al [16] TM/167 patients Prospective Significant relationship between myocardial iron and LVEF (r = 0.57, P < 0.001) / Tanner et al [60] TM/67 patients Cross sectional Myocardial T2* related to LV diastolic function (EPFR, r = -0.20, P = 0.19; APFR, r = 0.49, P < 0.001; EPFR/APFR ratio, r = -0.62, P < 0.001) / Westwood et al [52] TM/33 patients Cross sectional Good correlation of DT, Tei index and E/Em index with cardiac T2* values (P < 0.05, r = 0.70-0.81) and weak correlation of E/A with T2* (P < 0.05, r = -0.44) / Barzin et al [84] TM/47 patients Retrospective Significant correlations of the myocardial T2* with LVESVi and LVEDVi (r = -0.32, P = 0.027; r = -0.29, P = 0.046, respectively) / Bayraktaroğlu et al [22] TM/19 patients, SCD/17 patients…”
Section: Non-transferrin-bound Ironmentioning
confidence: 99%
“…Several studies indicated that serum ferritin was not correlated with cardiac T2* [16,22,57,58] . However, other studies with larger population size showed a weak relationship between serum ferritin and heart T2* [56,[59][60][61] .…”
Section: Non-transferrin-bound Ironmentioning
confidence: 99%
“…Although liver iron is a surrogate for total body iron burden and has been used for years to monitor chelation therapy among thalassaemia patients, it is a poor predictor of cardiac iron status [22]. The extrahepatic tissues of the pancreas and heart selectively load circulating NTBI, which is different from the hepatic iron load with transferrin-bound iron [23].…”
Section: Discussionmentioning
confidence: 99%